Atom probe tomography analysis of the distribution of rhenium in nickel alloys - Mottura, A; Warnken, N; Miller, M; Finnis, M; Reed, R (2010)
Atom probe tomography (APT) is used to characterise the distributions of rhenium in a binary Ni-Re alloy and the nickel-based single-crystal CMSX-4 superalloy. A purpose-built algorithm is developed to quantify the size distribution of solute clusters, and applied to the APT datasets to critique the hypothesis that rhenium is prone to the formation of clusters in these systems. No evidence is found to indicate that rhenium forms solute clusters above the level expected from random fluctuations. In CMSX-4, enrichment of Re is detected in the matrix phase close to the matrix/precipitate (γ/γ′) phase boundaries. Phase field modelling indicates that this is due to the migration of the γ/γ′ interface during cooling from the temperature of operation. Thus, neither clustering of rhenium nor interface enrichments can be the cause of the enhancement in high temperature mechanical properties conferred by rhenium alloying. © 2009 Acta Materialia Inc.